2014
DOI: 10.1371/journal.pone.0091021
|View full text |Cite
|
Sign up to set email alerts
|

Biotic Control of Skeletal Growth by Scleractinian Corals in Aragonite–Calcite Seas

Abstract: Modern scleractinian coral skeletons are commonly composed of aragonite, the orthorhombic form of CaCO3. Under certain conditions, modern corals produce calcite as a secondary precipitate to fill pore space. However, coral construction of primary skeletons from calcite has yet to be demonstrated. We report a calcitic primary skeleton produced by the modern scleractinian coral Acropora tenuis. When uncalcified juveniles were incubated from the larval stage in seawater with low mMg/Ca levels, the juveniles const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 35 publications
6
38
1
Order By: Relevance
“…This has been explained by a possible role of Mg in stabilizing the amorphous calcium carbonate nanoparticles serving as the building blocks of CoC (Mass et al, 2017;Von Euw et al, 2017). This is further supported by reports that corals grown in seawater with low Mg/Ca ratios produce skeletons with a high proportion of calcite (Higuchi et al, 2014), indicating an important role of Mg in stabilizing the prevalent aragonitic form of modern-day corals. While Mg content in fibrous aragonite is distinctly lower than in the CoC, a clear banding pattern in Mg/Ca ratio in these structures has been demonstrated by microscale measurement in multiple coral species (Meibom et al, 2004(Meibom et al, , 2007(Meibom et al, , 2008Gagnon et al, 2007;Frankowiak et al, 2016), suggesting Mg is concentrated at the interfaces between adjacent fibrous aragonite layers (Frankowiak et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…This has been explained by a possible role of Mg in stabilizing the amorphous calcium carbonate nanoparticles serving as the building blocks of CoC (Mass et al, 2017;Von Euw et al, 2017). This is further supported by reports that corals grown in seawater with low Mg/Ca ratios produce skeletons with a high proportion of calcite (Higuchi et al, 2014), indicating an important role of Mg in stabilizing the prevalent aragonitic form of modern-day corals. While Mg content in fibrous aragonite is distinctly lower than in the CoC, a clear banding pattern in Mg/Ca ratio in these structures has been demonstrated by microscale measurement in multiple coral species (Meibom et al, 2004(Meibom et al, , 2007(Meibom et al, , 2008Gagnon et al, 2007;Frankowiak et al, 2016), suggesting Mg is concentrated at the interfaces between adjacent fibrous aragonite layers (Frankowiak et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…In the calcification process of scleractinian corals, the taxon-specific composition of such molecules may influence the threshold at which seawater Mg/Ca can induce polymorphic change, as observed in mollusks (e.g., Falini et al, 1996). Higuchi et al (2014) observed partially calcitic (~20% ) primary skeletons produced by juvenile Acropora incubated in low Mg/Ca seawater from the larval stage. Nevertheless, the majority of the initial and post-initial skeleton was still aragonitic, suggesting that either some corals have both aragonite-and calcite-forcing organic matrix genes (Higuchi et al, 2014), the expression of which is less controlled and modulated during early ontogenetic development (note that many bryozoans and molluscs are capable of controlling CaCO 3 polymorphism within a single shell; e.g., Sandberg, 1975;Marin et al, 2008), or the initial stages of Acropora calcification are generally less controlled, permitting essentially induced biomineralization of certain carbonate structures to take place (Gilis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, genes involved in carbonate chemistry of the calcifying fluid, such as Ca ATPase (Zoccola et al 2004) and bicarbonate anion transporter (Zoccola et al 2015), were in neither the top 50 up-or down-regulated genes, nor the full list of DE genes. Thus, we propose that change in mMg/Ca in seawater did not impact the carbonate chemistry of the calcifying fluid, although the calcification rate decreased with low Mg/Ca seawater (Higuchi et al 2014;Higuchi et al 2017).…”
Section: Discussionmentioning
confidence: 86%